DINAMIKA DALAM SUKSESI KEPEMIMPINAN KOMITE NASIONAL PEMUDA INDONESIA (KNPI) PROVINSI RIAU TAHUN 2014 - Maulana Zusma; Auradian Marta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
In this research theres intersting phenomenas in leadership succession at Riau KNPI 2014th. i.e, the leader KNPI choosen by acclamation. The history proving that belongs 3 years of period, this is the first time the election of leader KNPI choosen by acclamation. This because the recession one of candidate of leader KNPI from 2 candidates that pass the verification. The recession was doing by Nasaruddin. The reason of recession was illogical, that he’s going vacation to the other towns and thats not ethical if Nasaruddin keep forward in that succesion. Afterward theres an other intersting facts that presence of Pancasila Youth Society Organisation in the forum implementation of DPD KNPI Riau Province XIII. Need to know that Youth Pancasila was not included in the participant invitation or participant observer in forum Riau Province KNPI 2014.Theory (approachability) that the writer using as a analysis tools in this research is the theory about Lobby and authorities. Whereas the method that writer use is qualitatively method and type of research is description, i.e sought to analysis the dynamics and giving explanation data that get from observation result. Which aim to emphasize and substantive an theory so get the information about current situation. The technique collecting data in this research is using interview technique and documentation study.Based on the research results and analysis the writers get three basic conclutions. First, democracy process in period XIII of KNPI 2014 not showing a good process and ideal. Second, KNPI of Riau Province, in this case committee of MUSPROV XIII KNPI Riau Province does not do public transparency to information of actual cause by the Nasaruddin recession from second candidates of election. And third, in leadership succession of Riau KNPI, purely the result of kongkalikong between Ari Nugroho side and Nasaruddin.Keywords : Dynamics, Leadership Succession and KNPI